Unveiling the actual progress of Digital Building Permit: Getting awareness through a critical state of the art review. (1st April 2022) - Noardo, Francesca; Guler, Dogus; Fauth, Judith; Malacarne, Giada; Mastrolembo Ventura, Silvia; Azenha, Miguel; Olsson, Per-Ola; Senger, Lennart
Abstract: Growing interest is awarded to the digitalization of the building permitting use case and many works are developed about the topic. However, the subject is very complex and many aspects are usually tackled separately, making it very hard for traditional literature reviews to grasp the actual progress in the overall topic. This paper unveils the detailed state of the art in Digital Building Permitting (DBP) by critically analysing the literature by means of a set of coding tags (research progress, implementation, affected DBP workflow steps, ambitions addressed) assigned by a multidisciplinary team. The executed research shows that the mainly addressed aspects of the digitalization of building permit process are the technologies to check the compliance of design proposals against regulations, followed by the digitalization of regulations. Improvable aspects identified in the entire building permit system are instead e.g. the involvement of officers, scalability of solutions and interoperability of data, intended both as data validation and as integration of geospatial data with building models. Highlights: There is an ever-increasing interest in digital building permit worldwide. The literature mainly focuses on BIM-based automated code compliance checking. Application content review (incl. regulation check and reports) is the focal point. Machine-readable building codes and interoperability are the key requirements. Gaps are in mindset change of officers and data interoperability and integration.